IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (Studi Analisis Implementasi Manajemen Berbasis Sekolah pada SMP Negeri 13 Sarolangun) - Syamsul Huda (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Principal performance against the various tasks and functions of the head of school as the principal as administrator edukator, Manager, supervisor, leader, innovator and motivator is running optimally. The performance of teachers viewed from four aspects assessed i.e. completeness program teaching teachers, presenting lessons learned evaluation and analysis of results the pupils as well as program improvement and enrichment. Of the four aforementioned aspects specifically on program improvements and enrichment there are still weaknesses such as the preparation of a test and the material over and over again at each school, which shows that the level of creativity of teachers compile the material is still very limited. The participation of the community against the school officials have not yet fully demonstrated good cooperation is caused by the low academic ability Community Association (School Committee) so it has limited plays an active role in activities such as academic nature, the formulation of the mission, the vision in planning and supervision mechanism in the implementation of the management of the school. As for the supporting factors of implementing school-based management in SMP Negeri 13 Sarolangun, among others: the existence of a partnership between the school principal by all of the partieswho are in the school, a large Fund of support which can be technically or conceptually so that the implementation of school-based management reflect the democratization of education. Keywords: analysis, implementation, school-based management.